Toward Sustainability Tourism: An ARDL Analysis of the Differential Impacts of International Tourism and Air Transport on CO2 Emissions in Thailand - Chandra Mandira, I. Made; Priyadi, Unggul; Wong, Wing-Keung (International Journal of Energy Economics and Policy, 2025)
This study investigates the differential impacts of international tourism and air transport on CO2 emissions in Thailand by employing the Autoregressive Distributed Lag (ARDL) approach. Analyzing data from 1995 to 2020, the findings indicate a significant negative correlation between international tourism and CO2 emissions, suggesting that increased tourist arrivals can lead to enhanced environmental efficiency under specific conditions. Conversely, air passenger numbers demonstrate a direct positive relationship with CO2 emissions in the short term, pointing to the inherent greenhouse gas intensity associated with air travel. The high explanatory power of the ARDL model, with an adjusted R-squared of 0.971397, emphasizes the robustness of these results, although caution is advised in interpreting the P-values due to the potential biases from automated model selection processes. These insights contribute to the broader understanding of how tourism dynamics interact with environmental outcomes, particularly in countries like Thailand, which heavily rely on tourism for economic growth. The implications highlight the urgent need for policies that balance tourism development with sustainability mandates, ultimately guiding Thailand’s trajectory toward carbon neutrality and sustainable tourism practices.